Empirical study on the performance of Malaysia real estate investment / Nurul Ain Badriah Abdul Kader - Abdul Kader, Nurul Ain Badriah (Faculty of Business and Management, 2015)
The title of this study is “Empirical Study on the Performance of Malaysia Real Estate Investment”. This study is to examine the factors that influence the total investment in Malaysia real estate. Year by year, the price in Malaysia property keep increasing parallel with it demand, however the performance of this type of investment are fluctuate according to macroeconomics condition of a country. In addition, this study will help the investors, regulators or speculators to know what are the factors that influence the investment in Malaysia real estate. In this study, factors are actually just focus on the macroeconomics condition not the factors from investment company itself. The data that represent the macroeconomics condition are collected was gross domestic products (GDP), interest rate, taxation and base lending rate (BLR) as independent variables while Malaysia total investment in real estate as dependent variable. The result of the study will further explain in this study.